Frontiers of the Roman Empire the upper Germanic Limes = Grenzen des Römischen Reiches = Frontières de l'Empire Romain : le limes de Germanie supérieure - Breeze, David J. 1944-; Thiel, Andreas 1964-; Roth, Sarah 1987-; Becker, Thomas 1971- (Archaeopress Archaeology, 2022)
This text illustrates the historical and archaeological significance of the Upper Germanic Limes and provides an up-to-date overview of its manifold features in the field
Also issued in print: 2022
"This work is licensed under the Creative Commons Attribution-NonCommerical-NoDerivatives 4.0 International License"--Title page verso
Includes bibliographical references
Zielgruppe: Specialized
Keywords: Limes (Roman boundary) / Germany; Excavations (Archaeology) / Germany; Germany / Antiquities, Roman; Germany / History / To 843; Rome / History / Germanic Invasions, 3rd-6th centuries; Rome / History / Empire, 30 B.C.-476 A.D